O sentido pedagógico da criatividade: um estudo sobre a imaginação e pensamento criativo em Vigotski e Lipman - Neves, Esther Almeida das (2024)
This dissertation is linked to the Fundamentals of Education line of the Postgraduate Program in Education at the University of Passo Fundo. The study focuses on the meaning of creativity in the pedagogical field. The central questioning of the investigation is based on the following question: Given the ever-present threat of discourses of mystification of creativity, which tend to mischaracterize its educational dimension, what is the uniqueness of its promotion in the school context? The answer to this question is sought in the thinking of Vygotsky and Lipman, especially in the notions of imagination and creative thinking. The general objective is to reaffirm the pedagogical meaning of creativity, associated mainly with imagination and creative thinking, as a humanizing process that demands some degree of directiveness. In addition to this broader objective, the following specific objectives were established: identify understandings about creativity in the past and present, as well as understanding its contributions to children's development and learning processes; explore the potential of playing and research to promote creativity at school, based, respectively, on Vygotski and Lipman; to demarcate, with the support of these authors, the specificity of creativity in the educational field and the conditions for its promotion in the school environment. The research, of a bibliographic nature, was supported by the hermeneutic methodological procedure which, according to Bachelard (1996), uses linguistic processes (text) and understanding the world in which human beings are inserted, contemplating their challenges and problems, as well as the interpretations regarding them. The text is divided into three chapters. In the first, there is a general overview of creativity in the educational context, its taboos, relevance and formative meaning, reserving space for the presentation of the Vygotskian perspective on imagination. In the second, we seek to deepen the reflection on creativity, looking at two of its main educational areas, namely, playing (Vygotsky) and investigating (Lipman). We seek to give special emphasis to the concept of research community as a pedagogical proposal that contributes to the development of creative and critical thinking, essential for the training of citizens in favor of a democratic society. In the third and final chapter, based on Vygotski and Lipman, an educational meaning for creativity is outlined, while conditions for promoting creativity in the school environment are also highlighted.